Active actuator fault‐tolerant control of a wind turbine benchmark model. (12th April 2013) - Simani, S.; Castaldi, P.; Odgaard, P. F.; Aubrun, C.; Majanne, Y.
SUMMARY This paper describes the design of an active fault‐tolerant control scheme that is applied to the actuator of a wind turbine benchmark. The methodology is based on adaptive filters obtained via the nonlinear geometric approach, which allows to obtain interesting decoupling property with respect to uncertainty affecting the wind turbine system. The controller accommodation scheme exploits the on‐line estimate of the actuator fault signal generated by the adaptive filters. The nonlinearity of the wind turbine model is described by the mapping to the power conversion ratio from tip‐speed ratio and blade pitch angles. This mapping represents the aerodynamic uncertainty, and usually is not known in analytical form, but in general represented by approximated two‐dimensional maps (i.e. look‐up tables). Therefore, this paper suggests a scheme to estimate this power conversion ratio in an analytical form by means of a two‐dimensional polynomial, which is subsequently used for designing the active fault‐tolerant control scheme. The wind turbine power generating unit of a grid is considered as a benchmark to show the design procedure, including the aspects of the nonlinear disturbance decoupling method, as well as the viability of the proposed approach. Extensive simulations of the benchmark process are practical tools for assessing experimentally the features of the developed actuator fault‐tolerant control scheme, in the presence of modelling and measurement errors. Comparisons with different fault‐tolerant schemes serve to highlight the advantages and drawbacks of the proposed methodology. Copyright © 2013 John Wiley & Sons, Ltd.